Generation and Transmission of High Symbol Rate Single Carrier Electronically Time-Division Multiplexing Signals - Junwen Zhang; Jianjun Yu (IEEE Photonics Journal)
We experimentally investigate the generation and transmission of high-symbol-rate single-carrier signals based on the electronically time-division multiplexing (ETDM) method. We have successfully increased the operating bandwidth limit of ETDM-based optoelectronic subsystems to the symbol rate of 128.8 and 138.4 GBaud over a long-haul SMF-28 link. We experimentally demonstrate 8 $×$ 128.8 Gbaud polarization-division multiplexed quadrature phase-shift keying (PDM-QPSK) signals over 2800 km SMF-28 and 4 $×$ 138.4 GBaud over 1200 km with EDFA-only amplification. To the best of our knowledge, 138.4 GBaud is the highest symbol rate of all-ETDM-based optical coherent system reported so far.